2009
DOI: 10.1007/s11085-009-9150-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Corrosion Resistance of Fe–Al–Cr Alloys in Simulated Low NO x Environments

Abstract: The first part of this manuscript presented SEM analysis of corrosion products formed on iron-aluminum-chromium alloys that were exposed to a simulated low NO x combustion environments. In Part II, results from electron microprobe analysis (EMPA) and scanning transmission electron microscopy (STEM) analyses of select as-corroded coupons from the long tem tests are discussed. Despite the formation of thick iron sulfide films one of the alloys, EMPA did not detect any measurable depletion of aluminum near the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Corrosion resistance experiments for Fe-Cr-Al alloys show Cr depletion in the Fe-10Al-5Cr alloy. 30 In the oxidation experiments of Fe 3 Al-͑0,2,4,6%͒Cr alloys a Cr-free region was observed. 31 In low Al or Si iron-chromium alloys the inward growth of Cr 2 O 3 was deduced to be initiated due to FIG.…”
mentioning
confidence: 97%
“…Corrosion resistance experiments for Fe-Cr-Al alloys show Cr depletion in the Fe-10Al-5Cr alloy. 30 In the oxidation experiments of Fe 3 Al-͑0,2,4,6%͒Cr alloys a Cr-free region was observed. 31 In low Al or Si iron-chromium alloys the inward growth of Cr 2 O 3 was deduced to be initiated due to FIG.…”
mentioning
confidence: 97%
“…Clearly, the addition of chromium was beneficial, but whether it was due to the formation of Cr 2 O 3 or to the chromium affecting the formation of Al 2 O 3 , for example, could not be determined in the present work. A more detailed description and analytical electron microscopy analysis of the role of chromium on the Fe-12.5Al alloy is presented in Part II of this work [23].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the typical non-protective nature of iron sulfides on iron aluminum alloys, it is concluded that a more protective layer eventually formed underneath the iron sulfide film and acted as a sufficient diffusion barrier to inhibit the transport of either sulfur or iron ions through the scale. Further examination of the scale development on this alloy is presented in Part II [23].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, slurry aluminides have been exposed to steam for over 22,000 h in the bypass of a steam turbine at 640 °C and 180 bar without substrate degradation and under laboratory testing conditions (100% steam, 650 °C, 1 bar) the same coatings have reached 50,000 h of exposure (the test is still ongoing) . DuPont et al have also demonstrated that FeCrAl containing alloys exhibit an outstanding corrosion resistance in sulfidizing and oxidizing conditions due to the formation of a protective Al 2 O 3 scale stabilized by the presence of Cr .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, FeCrAl alloys are currently under study due to their low cost and excellent corrosion resistance. However there are still weldability issues that need to be addressed .…”
Section: Introductionmentioning
confidence: 99%